نظرية المعرفة بين السوفسطائيين وأفلاطون وأثرها في فلسفة التربية - محمد، محمود علي (جامعه دمشق - كليه التربية, 2022)
هدف البحث إلى إيضاح نظرية المعرفة عند أفلاطون والسفسطائيين، وبيان أثرها في فلسفة التربية، ولتحقيق هذا الهدف عرض الباحث نظرية المعرفة عند السفسطائيين التي تتلخص في أن المعرفة إدراك حسي يقوم الإنسان بتحصيلها بواسطة الحواس، وأن الإنسان مقياس وجود الحقائق والأشياء، والمعرفة عندهم نسبية، ولها دور مهم في الترقي الأخلاقي، وهي حق لكل إنسان وليست حكرا على الأقلية الأرستقراطية. أما أفلاطون فقدم نظرية في المعرفة تتلخص في أن المعرفة نتاج العقل. فبرأيه هناك عالمان: عالم الحس الذي نعيش فيه، وعالم المثل، يقوم العقل من خلال الجدل بالوصول إلى عالم المعاني العقلية أو عالم المثل من خلال الجدل الصاعد الذي يرتقي به الفرد من فكرة إلى فكرة بوساطة فكرة حتى يصل إلى فكرة الخير المطلق أو الله، وبعد أن يتعرف العقل على المثل يهبط إلى الأشياء ليتعرف عليها عبر الجدل النازل، وللمعرفة عند أفلاطون أربع درجات: درجة الإحساس ودرجة الظن ودرجة الاستدلال ودرجة التعقل. اتفق أفلاطون والسفسطائيون في أن المعرفة ممكنة لكنها إدراك حسي عند السفسطائيين، وتذكر عند أفلاطون، وأنهما معا وجها الأنظار من الطبيعة الخارجية إلى الطبيعة البشرية، واختلفا في غاية المعرفة وكيفية حصولها، ومقياس وجودها وصحتها، وفي كونها مطلقة عند أفلاطون، ونسبية عند السفسطائيين. تركت نظرية المعرفة آثارا عديدة في فلسفة التربية منها توجيه الأنظار إلى دور الحواس في المعرفة عند السفسطائيين، ودور العقل فيها عند أفلاطون، وإلى القيمة النفعية للمعرفة، وإلى الصلة الدائمة بين إصلاح المعرفة والإصلاح السياسي والتربوي، ودور المعرفة في الترقي الأخلاقي، وضرورة إشراف الدولة على التربية. The research aimed to define Plato’s and the sophists theory of knowledge and to clarify its effects on the philosophy of education. To achieve this objective, the researcher reviewed the theory of knowledge among the sophists which states that knowledge is perceptions collected by man using his senses. The man is the standard of the existence of the facts and the objects. Their theory states that knowledge is relative and has an important role in the ethical promotion. The sophists consider that knowledge is a right for each human and it is not exclusive for the rich and aristocratic class. Plato represented a theory of knowledge which states that knowledge is an outcome of the mind. In his opinion, there are two distinct worlds: the world of senses which we live in and the ideal world. The mind reaches the ideal world through the ascending argument by which the human progresses from an idea to another using his mind until he reaches the absolute goodness (the god). After recognizing the ideals, man descends to the objects to recognize them through the descending argument. According to Plato, there are four stages of knowledge development: sensation, the belief, the thinking and the reason (perfect intelligence). Plato and the sophists do agree that knowledge is possible but it is perception in the sophists theory while it is mind according to Plato's theory. Plato and the sophists have drawn the attention from the external nature to the human nature. They also differed in the objectives of knowledge, the modality to get it, the standard of its existence and correctness and the fact that it is relative according to the sophists and absolute according to Plato.
Keywords: فلسفة السفسطائيين -- الشواهد الفلسفية -- الفكر التربوي